Flow Cytometry for Diagnosis of Primary Immune Deficiencies—A Tertiary Center Experience From North India - Rawat, Amit; Arora, Kanika; Shandilya, Jitendra; Vignesh, Pandiarajan; Suri, Deepti; Kaur, Gurjit; Rikhi, Rashmi; Joshi, Vibhu; Das, Jhumki; Mathew, Babu; Singh, Surjit (Frontiers in Immunology, 2019)
Flow cytometry has emerged as a useful technology that has facilitated our understanding of human immune system. Primary immune deficiency disorders (PIDDs) are a heterogenous group of inherited disorders affecting the immune system. More than 350 genes causing various PIDDs have been identified. Whilst the initial suspicion and recognition of PIDDs is clinical, laboratory tools such as flow cytometry and genetic sequencing are essential for confirmation and categorization. Genetic sequencing, however, are prohibitively expensive and not readily available in resource constrained settings. Flow cytometry remains a simple, yet powerful, tool for multi-parametric analysis of cells. While it is confirmatory of diagnosis in certain conditions, in others it helps in narrowing the list of putative genes to be analysed. The utility of flow cytometry in diagnosis of PIDDs can be divided into four major categories: a). Enumeration of lymphocyte subsets in peripheral blood b). Detection of intracellular signalling molecules, transcription factors and cytokines c). Functional assessment of adaptive and innate immune cells (e.g. T cell function in severe combined immune deficiency and natural killer cell function in familial hemophagocytic lymphohistiocytosis d). Evaluation of normal biological processes (e.g. class switching in B cells by B cell immunophenotyping). This review focuses on use of flow cytometry in disease specific diagnosis of PIDDs in the context of a developing country.